Herpes Zoster and Postherpetic Neuralgia: Changing Incidence Rates From 1994 to 2018 in the United States. (23rd August 2020) - Thompson, Ryan R; Kong, Christina L; Porco, Travis C; Kim, Eric; Ebert, Caleb D; Acharya, Nisha R
Abstract: Background: The incidence of herpes zoster (HZ) has been increasing in recent decades. Although 2 vaccines for HZ are available, there have been few studies on the incidence rates of HZ and postherpetic neuralgia (PHN) since their introduction. This study examined the incidence rates of HZ and PHN from 1994 to 2018 in the United States to determine if they have continued to increase since introduction of the HZ vaccines. Methods: A de-identified longitudinal administrative claims database, the OptumLabs Data Warehouse, was used to assess incidence rates among individuals continuously enrolled in the database for ≥365 days with no prior history of HZ or PHN. Unstandardized and standardized incidence rates were calculated by year, 10-year age groups, sex, and race/ethnicity. Results: There were 610 766 individuals with HZ (median age, 56.3; interquartile range, 43.0–68.7 years; 59.8% women; 70.6% white). From 1994 to 2018, the incidence of HZ increased from 286.0 (95% confidence interval [CI], 259.1–312.8) to 579.6 (95% CI, 554.2–605.0) cases per 100 000 person-years, an annual increase of 3.1% (95% CI, 2.5–3.6%). Since 2007, annual HZ incidence rates have decreased in individuals ≤20 and >60 years old. The overall incidence rate of PHN was 57.5 (95% CI, 56.0–59.0) cases per 100 000 person-years. The proportion of individuals with HZ who developed PHN was higher from 2007 to 2018 than from 1994 to 2006. Conclusions: HZ incidence rates have continued to increase in age groups for which HZ vaccines are not currently recommended, warranting a review of current vaccine recommendations. Abstract : The incidence rates of herpes zoster and postherpetic neuralgia increased overall in the United States from 1994 to 2018. Since 2007, the observed herpes zoster incidence rates have begun to decline in the youngest and oldest age groups.